Good Practices in Model‐Informed Drug Discovery and Development: Practice, Application, and Documentation. (14th March 2016) - ,; Marshall, SF; Burghaus, R; Cosson, V; Cheung, SYA; Chenel, M; DellaPasqua, O; Frey, N; Hamrén, B; Harnisch, L; Ivanow, F; Kerbusch, T; et al.
Abstract : This document was developed to enable greater consistency in the practice, application, and documentation of Model‐Informed Drug Discovery and Development (MID3) across the pharmaceutical industry. A collection of "good practice" recommendations are assembled here in order to minimize the heterogeneity in both the quality and content of MID3 implementation and documentation. The three major objectives of this white paper are to: i) informcompany decision makers how the strategic integration of MID3 can benefit R&D efficiency; ii) provideMID3 analysts with sufficient material to enhance the planning, rigor, and consistency of the application of MID3; and iii) provideregulatory authorities with substrate to develop MID3 related and/or MID3 enabled guidelines.